Location of Transportation Districts at Modeling of Transportation Processes in a Region - Petr Cenek; Jaroslav Janacek; Ludmila Janosikova (Communications - Scientific letters of the University of Zilina, 2002)
Transportation planning should frequently work with too many places, where transportation demands arise (dwelling places in a region). That is why it is necessary to reduce the total number of such places in a transportation network on a given number of transportation districts. An algorithm for automatic location of transportation districts is described in the paper. The location of transportation districts can be defined using mathematical model of the uncapacitatedlocation problem, which can be solved using an exact algorithm. Several criteria are proposed according to which an optimal location of transportation districts is calculated. The results of calculations were compared with the hand-made solution of an expert.